Penanggulangan Human Trafficking Di Indonesia - Syugiarto Syugiarto (Jurnal ADMINISTRATOR, 2022)
This study aims to determine the causes of human trafficking by using the hierarchical analysis scheme proposed by Dunn (2003 & 2018) and to find solutions to these problems by mapping the actors involved in the process of formulating policies for overcoming human trafficking. This research itself uses a type of qualitative research with a literature study method. The results of the study indicate that the causes of human trafficking are economic factors, education of victims of human trafficking and the government. Economic factors are the reason for people to become TKI / TKW abroad, but there are some distribution agents who are not responsible so that the level of human trafficking is getting higher. The low level of education and lack of public knowledge related to human trafficking are the main causes that cause human trafficking in Indonesia to reach 582 people in 2019. The weak implementation of Law Number 21 of 2007 carried out by the government is one of the factors for the high level of human trafficking. in Indonesia. In addition, it is also known that the process of formulating policies to combat Human Trafficking in Indonesia involves several actors, including: Ministry of Women's Empowerment and Child Protection, Legislators / Politicians, Ministry of Education and Culture, Academics, TNI / POLRI, Mass Media, Manpower Distribution Agencies Overseas, NGOs / NGOs and the community as parties who have a high probability of becoming victims of human trafficking.